The effects of substratum material and surface orientation on the developing epibenthic community on a designed artificial reef. Issue 9 (20th October 2016) - Ushiama, Shinjiro; Smith, James A.; Suthers, Iain M.; Lowry, Michael; Johnston, Emma L.
Abstract: Artificial reefs provide shelter and can be an important source of food for fish depending on the epibenthic community on the structure. The growth and diversity of this community is influenced by the substratum material and the surface orientation of the reef. Settlement plates of four materials (Perspex, sandstone, wood and steel) were deployed in three orientations (upwards, downwards and vertical) at a depth of 33 m on a designed artificial reef (DAR) off the coast of Sydney, Australia. After three months, the steel surfaces had lower invertebrate species richness, total abundance and diversity compared to other surfaces. Steel was not an ideal material for the initial recruitment and growth of epibenthic invertebrates. A longer duration would be required to develop a mature epibenthic community. Surface orientation had species-specific impacts. Surface material and orientation are important factors for developing epibenthic assemblages, and are thus likely to affect the broader artificial reef assemblage, including fish.